2021
DOI: 10.1007/s40520-021-01993-x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Frailty Index in centenarians

Abstract: This study measured the subclinical frailty of centenarians by looking at the accumulation of their biological abnormalities. For this aim, a biological Frailty Index (FI) was computed in centenarians living in Northern Italy. The median value of the biological FI was 0.33 (interquartile range, IQR 0.28–0.41). The biological FI did not significantly differ between women (0.34, IQR 0.31–0.39) and men (0.32, IQR 0.26–0.43). The biological FI seems to have a narrower distribution compared to clinical FI we previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A clinical FI is also able to significantly predict self-rated health and Instrumental Activities of Daily Living (IADL) dependency beyond the effect of age and gender in a cohort of Chinese centenarians 23 . Interestingly, in the Northern Italy cohort, a FI built on biological parameters showed average lower values (median value of 0.33) and a narrower distribution (from 0.11 to 0.69) than the clinical one 24 . The data observed in these centenarians are amazing, if we consider that in older persons the biological FI generally shows higher values than those of the clinical FI, since biological FI anticipates the changes in health status before the manifestation of the clinical deficits 25,26 .…”
Section: Frailty and Longevitymentioning
confidence: 88%
“…A clinical FI is also able to significantly predict self-rated health and Instrumental Activities of Daily Living (IADL) dependency beyond the effect of age and gender in a cohort of Chinese centenarians 23 . Interestingly, in the Northern Italy cohort, a FI built on biological parameters showed average lower values (median value of 0.33) and a narrower distribution (from 0.11 to 0.69) than the clinical one 24 . The data observed in these centenarians are amazing, if we consider that in older persons the biological FI generally shows higher values than those of the clinical FI, since biological FI anticipates the changes in health status before the manifestation of the clinical deficits 25,26 .…”
Section: Frailty and Longevitymentioning
confidence: 88%
“…Octogenarians, nonagenarians, and centenarians are special populations of older adults who escape the fate of usual aging and have increased biological reserves, but at the same time are exposed to an extremely high risk of frailty. Therefore, there have been attempts to develop frailty diagnostic instruments dedicated to long-lived individuals, including laboratory biomarkers of biological frailty [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental and lifestyle factors can have differential effects on the clinical profile and epigenetic status over the course of a person's life [23]. Consequently, as a result, long livers constitute a highly heterogeneous population, encompassing individuals in both good and very poor health statuses, as demonstrated by the varying degrees of frailty [24]. Several previous studies have explored the association between epigenetically determined age and frailty, and these studies have confirmed a strong link between prevalent frailty and epigenetic age [25].…”
Section: Discussionmentioning
confidence: 99%